RESULTS OF ANALYSIS OF THE POLLUTION STATE OF WATER RESERVOIRS IN MODERN CONDITIONS - G.F.Sherkoziyeva; M.N.Bahriddinova; B.M.Toshpulatov; M.R.Boysariyeva; Z.Z.Egamberdiyeva; D.J.Abdurakhimova; S.S.Rasulov (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Annotation. The article analyzes the current state of pollution of open water bodies. According to the analysis of the literature and personal observations, the water of water bodies is mainly polluted with sulfates and iron. At the same time, water oxidation and turbidity are also considered to be the main water quality indicators.